2009
DOI: 10.1080/13548500902890095
|View full text |Cite
|
Sign up to set email alerts
|

Why most Togolese people do not seek care for malaria in health care facilities: A theory-driven inventory of reasons

Abstract: Using a broad theory of human motivation, the study examined the psychological structure of the reasons evoked by Togolese people for not attending medical facilities when they think they have malaria. Five hundred and thirty-two persons living in Lome, Togo were presented with a questionnaire of motives. Through exploratory and confirmatory factor analyses, a seven-factor structure of motives was found. Participants explained their reluctance to attend medical facilities by the facts that (a) malaria is not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…More than 80% of patients with fever in the intervention and control arms in both transmission settings consulted CHWs for treatment within 24 h after onset of symptoms, which is much higher than has previously been observed at health facilities in Uganda [11] and elsewhere [26]. These data show that CHWs provide an opportunity for improving the speed of treatment seeking for febrile illnesses in rural areas, where poor access to health facilities, lack of drugs, perceived high cost and unfriendly attitude of health workers often result in delayed treatment [27][28][29][30][31][32] and illustrate the role of community-based treatment programmes in increasing access to prompt effective treatment of malaria.…”
Section: Discussionmentioning
confidence: 83%
“…More than 80% of patients with fever in the intervention and control arms in both transmission settings consulted CHWs for treatment within 24 h after onset of symptoms, which is much higher than has previously been observed at health facilities in Uganda [11] and elsewhere [26]. These data show that CHWs provide an opportunity for improving the speed of treatment seeking for febrile illnesses in rural areas, where poor access to health facilities, lack of drugs, perceived high cost and unfriendly attitude of health workers often result in delayed treatment [27][28][29][30][31][32] and illustrate the role of community-based treatment programmes in increasing access to prompt effective treatment of malaria.…”
Section: Discussionmentioning
confidence: 83%
“…This study reveals that respondents who took non-prescribed anti-malarials, a higher proportion 56.1% took non-ACT, such as chloroquine, artemether, amodiaquine, quinine and sulphadoxine-pyrimethamine. This situation can be attributed to the lack of knowledge of chemical sellers about the effective treatment for malaria and are dispensing both ACT and non-ACT anti-malarial drugs to clients to treat malaria [4,6,17,18]. The study also found that children under five years of age were more likely to receive non-prescribed anti-malarials if others influenced their carer’s decision.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for using non-prescribed anti-malaria drugs include lack of access to health facilities, cost of treatment in health facilities and social distance of health workers from patients [6]. Several sociocultural factors, including people’s beliefs, perceptions and knowledge about malaria and influence of peers on people’s choice of malaria treatment [4,7] have been cited to influence use of non-prescribed anti-malarials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one of the strategies of the Roll Back Malaria (RBM) programme is to reduce mortality in U5 through early diagnosis and treatment within 24 hours of the onset of symptoms [ 5 ]. However, poor physical access to health facilities is an obstacle to early diagnostic and curative services in rural areas in Low- and Middle-Income Countries (LMICs) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%